THE ROLE OF HUMANIST THOUGHT IN BUILDING BRIDGES BETWEEN ISLAM AND UNIVERSAL HUMAN VALUES - Karimullah, Suud Sarim; Mahbubi, Mahbubi (IAIN Kendari, 2023)
This study traces the fundamental role of humanist thought in bridging the gap between Islamic values and the universality of human values. This study adopts a library research method that applies a literature analysis approach that is not only inclusive but also holistic in collecting, evaluating, and integrating findings from various literature sources that are relevant to the focus of the study. The results of the study highlight the positive contribution of humanist thinking in stretching the harmony between Islamic teachings and universal human values, being a driver in shaping an inclusive and sustainable world for all individuals, regardless of their religious or cultural diversity. The relationship between Islamic teachings and universal human values has shown a positive evolution, with humanist thought serving as an essential link that fosters interreligious dialogue and promotes tolerance. The influence of humanist thought in the structure of society and interreligious relations also creates an environment that promotes inclusiveness, sustainability, and peace. While challenges remain, humanist thinking remains a positive driver in shaping a better world for all human beings, regardless of their religious or cultural background.